Cross-Talk between AURKA and Plk1 in Mitotic Entry and Spindle Assembly - Asteriti, Italia Anna; De Mattia, Fabiola; Guarguaglini, Giulia (Frontiers in Oncology, 2015)
The Aurk-A kinase is involved in different aspects of mitotic control, from mitotic entry to cytokinesis. Consistent with its pleiotropic roles, several Aurk-A interactors are able to modulate its activity, the best characterised being the microtubule binding protein TPX2, the centrosomal protein Cep192 and Bora. Bora has been described as an essential cofactor of Aurk-A for phosphorylation-mediated activation of the mitotic kinase Plk1 at the G2/M transition. A complex Aurk-A/Plk1 signalling axis is emerging, with multiple involved actors; recent data suggest that this control network is not restricted to mitotic entry only, but operates throughout mitosis. Here, we integrate available data from the literature to depict the complex interplay between Aurk-A and Plk1 in G2 and mitosis and how it contributes to their mitotic functions. We will particularly focus on how the activity of specifically localized Aurk-A/Plk1 pools is modulated in time and space by their reciprocal regulation, to ensure the timely and coordinated unfolding of downstream mitotic events.